1996
DOI: 10.1007/bf02523367
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization at the double‐bond region of jojoba oil. 7. Chemical binding of jojoba liquid wax to polystyrene resins

Abstract: Jojoba wax was chemically bonded to a polystyrene matrixvia a stable C‐C covalent bond. This was achieved by binding allyl‐brominated jojoba derivatives to lithiated crosslinked polystyrene‐2% divinylbenzene or XAD‐4 polymeric beads via a nucleophilic substitution reaction. The double‐bond regions in the jojoba wax were preserved. A side reaction that accompanied the nucleophilic substitution was HBr elimination, which produced diene and triene systems in the bound jojoba. Phosphonation and sulfur chlorination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 6 publications
1
7
0
Order By: Relevance
“…It is also clearly seen that, the saturated fatty acid content was found to be 2.27% of the total acid content and the ratio of the saturated to unsaturated acids was found to be (1:43). These results are in a good accordance with the previous results reported by Moustafa [17] and Binman et al [18].…”
Section: Fatty Acid Compositionsupporting
confidence: 96%
“…It is also clearly seen that, the saturated fatty acid content was found to be 2.27% of the total acid content and the ratio of the saturated to unsaturated acids was found to be (1:43). These results are in a good accordance with the previous results reported by Moustafa [17] and Binman et al [18].…”
Section: Fatty Acid Compositionsupporting
confidence: 96%
“…The main application of jojoba wax is currently in cosmetics, but the wax and its derivatives have potential commercial uses in a variety of fields, including pharmaceuticals and lubrication (2,3). It was recently found that chemical binding of jojoba wax to a polystyrene matrix (4,5) followed by sulfurchlorination or phosphonation produced a solid suitable for use as an extractant for metal ions (6). This type of extractant has a number of advantages over resins impregnated with phosphonated and sulfurized jojoba wax derivatives, which have previously been used for extraction of metal ions, such as uranium and mercury (7)(8)(9), i.e., there were no problems of loss of expensive extractants or of contamination of aqueous solutions.…”
mentioning
confidence: 99%
“…The solid products were obtained as described in our preceding papers (3,4). 13 C NMR and 31 P NMR spectra in CDCl 3 solution were obtained on a Bruker DMX-500 MHz instrument (Karlsruhe, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…The 31 P signal of diethyl jojobylphosphonate XI (Table 3) in solution appeared at δ32.5, downfield from 85% H 3 PO 4 as the internal standard (8). In the solid-state VACP-MAS NMR spectrum of V (Scheme 1), three 31 P signals could be distinguished with chemical shift parameters (with respect to the phosphor line in 85% H 3 The isotropic chemical shift values of these MAS sideband patterns were 1.8, 17.5, and 24.5 ppm, respectively, with line widths of about 10 ppm and relative intensities about equal to 2:1:1. The 31 P spectrum of X (Scheme 2, n = 2) contained similar sideband patterns to the V spectrum, the only differences being a significant reduction of the chemical shift anisotropy of the first pattern and an increase of the widths of the center and sidebands of the second and third patterns by a factor of about two.…”
Section: Table 1 Chemical Shifts a Of 13 C Of Jojoba Oil (I) As Liquimentioning
confidence: 99%
See 1 more Smart Citation